2019
DOI: 10.1097/ceh.0000000000000251
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Experienced By North Korean Refugee Doctors in Acquiring a Medical License in South Korea: A Qualitative Analysis

Abstract: Introduction: In general, refugee doctors encounter difficulties in regularly practicing medicine in their host countries. In particular, many barriers impede the efforts of North Korean refugee doctors (NKRDs) who have settled in South Korea to acquire a medical license in the country. This study examines the experiences and opinions of NKRDs in their attempts to acquire permission to legally practice medicine in South Korea and the opinions of South Korean experts regarding this matter. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…They posited that bridging social capital (relationships across groups)—as opposed to bonding social capital (relationships within groups)—between IMGs and host country society was necessary for acculturation and upward mobility. We found that IMGs were aware of this, yet found it difficult at times 88 to form these bridging relationships and felt excluded 15,20,35,46,54,59,68,81 . We identified this isolation as part of the fourth barrier that IMGs face.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…They posited that bridging social capital (relationships across groups)—as opposed to bonding social capital (relationships within groups)—between IMGs and host country society was necessary for acculturation and upward mobility. We found that IMGs were aware of this, yet found it difficult at times 88 to form these bridging relationships and felt excluded 15,20,35,46,54,59,68,81 . We identified this isolation as part of the fourth barrier that IMGs face.…”
Section: Discussionmentioning
confidence: 86%
“…The cultural differences that IMGs faced included culture in the workplace and in society at large 15,16,20,36,39,46,54–56,58,59,65,69,72–83 . An IMG who was a native of the host country but qualified in another country did not suffer culture shock in society compared with an IMG who immigrated from another country 14,47,71,73 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations